Optimal dispatch of an electricity-heat virtual power plant based on Benders decomposition - Wu, Yunxia; Yang, Shenhao; Zhang, Su; Li, Longyuan; Yan, Xiaobin; Li, Jingxuan (Frontiers in Energy Research, 2024)
Recently, wind energy has been developed as an important technology to address the energy crisis. However, due to an unreasonable energy structure, wind power curtailment is becoming increasingly severe. Combined heat and power dispatch (CHPD) provided a solution for wind accommodation by utilizing the flexibility resources of district heating systems. Because of the imperfect dispatch methods and CHPD platforms, many wind power heating projects have not effectively linked the use of abandoned wind and heating. The virtual power plant (VPP) achieves the reasonable combination of controllable power sources, distributed energy, controllable loads, and energy storage systems within a certain area. Thus, we propose a VPP model based on combined dispatch of wind power and heat energy, which integrates wind turbines, thermal turbines, CHP units, etc., into a whole to join in the grid operation. Besides, to preserve the privacy of energy agents, Benders decomposition algorithm is adopted to solve the proposed model in this paper. The validity and efficiency of the proposed VPP model and Benders decomposition algorithm are verified via numerical cases.